ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PRODUK BROWNIES COKLAT PADA UD DHENOK GROUP - Aditya Prayudhi, Luhur; Zamrodah, Yuhanin (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2022)
The availability of cocoa beans is very large in the Blitar area so that it opens up considerable business opportunities for the people in Blitar. In addition, cocoa plants as a producer of cocoa beans can thrive in the Blitar area, making it easy to obtain raw materials. Processing of basic ingredients of chocolate in the Blitar area is still minimal, so it is very necessary to diversify products from chocolate. One of the products here is chocolate brownies where an effective marketing strategy is needed to increase sales of Chocolate Brownies. The purpose of this study was to determine the marketing strategy of Chocolate Brownies products with SWOT analysis. The marketing system carried out at UD Dheenok Group uses a direct marketing system, namely sales at industrial sites and indirectly by distributing products to Kampung Chocolate as a working partner in marketing. customers, while the weakness lies in unwritten financial administration, and does not have investors so that it has an impact on business development and the absence of visual promotion media such as advertisements. market due to the lack of similar products in Blitar City. The biggest threat faced in marketing chocolate brownies is the price of raw materials for eggs that fluctuates and the product expiration period is short, which is around 10 days. The marketing strategy used by UD Dheenok group in developing chocolate brownie processed food products is a business strategy, namely product excellence